2018
DOI: 10.1002/jcb.28157
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs‐107 inhibited autophagy, proliferation, and migration of breast cancer cells by targeting HMGB1

Abstract: Purpose To investigate the effects of microRNAs‐107 (miR‐107) on autophagy, proliferation, and migration of breast cancer cells and its mechanism by targeting high mobility group protein B1 (HMGB1). Methods Real‐time polymerase chain reaction assay was used to detect the expression of miR‐107 in breast cancer and its cell lines. In MDA‐MB‐231 and MDA‐MB‐453 breast cancer cells, the expression of p62, Beclin1 protein, and the changes of cell proliferation and migration after overexpression of m miR‐107 were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…The function of miRNAs during tumor growth and progression as well modulation of chemoresistance is diverse and complex. MiR-107 could induce or inhibit metastasis in different cancer types [24,25], while miR-200a-3p could influence different signaling pathways in hepatocellular carcinoma [29,30]. In the present study, we observed a similar or inversed regulation of six miRNAs in just two of the three BCSC lines considered.…”
Section: Discussionsupporting
confidence: 59%
“…The function of miRNAs during tumor growth and progression as well modulation of chemoresistance is diverse and complex. MiR-107 could induce or inhibit metastasis in different cancer types [24,25], while miR-200a-3p could influence different signaling pathways in hepatocellular carcinoma [29,30]. In the present study, we observed a similar or inversed regulation of six miRNAs in just two of the three BCSC lines considered.…”
Section: Discussionsupporting
confidence: 59%
“…In breast cancer, miR-129-5p direct regulation of HMGB1 and consequently of autophagy contributes to ameliorate radiosensitivity in vitro (185). Additionally, even though the effects on chemosensitivity were not evaluated, miR107 was found to be downregulated in human breast tumors and cell lines (196). This miR targets HMGB1 directly and regulates its autophagy inducing properties in vitro , while overexpression reduces tumorigenesis in vivo .…”
Section: Hmgb1 and Cancermentioning
confidence: 99%
“…High mobility group box 1 (HMGB1) is a regulator of autophagy as a ubiquitous nuclear protein, which can regulate and promote various DNA-related activities such as transcription, replication, and repair (28 30). Recently, studies indicated that HMGB1 plays an essential role in chemotherapy sensitivity through modulating protective autophagy in a number of cancers, including breast cancer (31,32). Thus, targeting HMGB1-mediated autophagy might improve the chemosensitivity of cancer cells.…”
Section: Introductionmentioning
confidence: 99%